he consequences of imbalance in Juan de Flores’ Grisel y Mirabella - Corry, Jennifer M. (Revista de Letras, 2007)
Juan de Flores’ roamance Grises y Mirabella (1945) contains sharps divisions between men and women that are portrayed through Justice and Mercy, and separation between the sexes. The author is careful to describe the division by constantly maintaining a distance between men and women both in private and public affairs. This separation leads to violence and chaos at the end of the narration despite a model of harmony and love demonstrated by the young Grisel and Mirabella. Through the portrayal of such separation and violence the author not only points out that society suffers when ruled only by masculine qualities but also advocates a balanced society in which the best values of both men and women may rule.